NADPH-generating dehydrogenases: their role in the mechanism of protection against nitro-oxidative stress induced by adverse environmental conditions - Corpas, Francisco J.; Barroso, Juan B. (Frontiers in Environmental Science, 2014)
NADPH is an essential reductive coenzyme in biosynthetic processes such as cell growth, proliferation and detoxification in eukaryotic cells. It is required by antioxidative systems such as the ascorbate-glutathione cycle and is also necessary for the generation of superoxide radicals by plant NADPH oxidases and for the generation of nitric oxide (NO) by L-arginine-dependent nitric oxide syntase. This coenzyme is principally re-generated by a group of NADP-dehydrogenases enzymes including glucose-6-phosphate dehydrogenase (G6PDH) and 6-phosphogluconate dehydrogenase (6PGDH), both belonging to the pentose phosphate pathway, the NADP-malic enzyme (NADP-ME) and NADP-isocitrate dehydrogenase (NADP-ICDH). In this study, current perspectives on these enzymes in higher plants under different stress situations are reviewed and it is also pointed out that this group of NADPH-generating dehydrogenases is a key element in supporting the mechanism of response to nitro-oxidative stress situations.